Sub-diffraction error mapping for localisation microscopy images - Richard J. Marsh (Nature Portfolio, 2021)
Determining the quality of localisation microscopy images is currently challenging. Here the authors report use of the Haar wavelet kernel analysis (HAWK) Method for the Assessment of Nanoscopy, termed HAWKMAN, to assess the reliability of localisation information.